The history of the unspeakable: Shimokawa Masaharu's The forgotten history of evacuation. Issue 4 (2nd October 2018) - Morgan, Jason
ABSTRACT: Histories of wartime Japan often focus on the Japanese home islands after Japan's surrender to Allied forces on 15 August 1945. Japanese citizens living in Korea, Manchuria, and elsewhere in the far-flung Japanese Empire are usually left out of the historiographical record. In a new book about the evacuees— hikiagesha —from the defunct Empire, Shimokawa Masaharu presents a vivid, harrowing portrait of the suffering of those who had to make their way back to Japan after the end of the Greater East Asia War. In particular, Shimokawa focuses on Izumi Sei'ichi, who established a sanatorium and abortuary in Fukuoka for women who had been raped by enemy soldiers.